2012
DOI: 10.2174/1874325001206010473
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Lumbosacral Dislocation: Case Report and a Comprehensive Review

Abstract: Lumbosacral fracture-dislocation is a rare occurrence. There are more than 73 cases reported in the English literature. We report on the imaging findings and surgical treatment in a patient suffered of unilateral traumatic L5-S1 dislocation associated with severe disruption of the posterior ligamentous complex. The patient underwent open reduction and stabilization of L4-S1 vertebrae with posterior instrumentation system. Open reduction and internal fixation was mandatory as post-traumatic ligamentous insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…[12][13][14][15] There is only one other reported case of a pure bilateral dislocation outside the lumbosacral junction in an adult. 4 Common to these injuries are the mechanism of a high-speed motor vehicle accident, associated multisystem injuries, including abdominal solid organ and hollow viscus injuries, and prevalence of neurological deficits (more common in bilateral facet dislocations 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] There is only one other reported case of a pure bilateral dislocation outside the lumbosacral junction in an adult. 4 Common to these injuries are the mechanism of a high-speed motor vehicle accident, associated multisystem injuries, including abdominal solid organ and hollow viscus injuries, and prevalence of neurological deficits (more common in bilateral facet dislocations 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Few reported cases have been described, and those that were typically involved the lumbosacral junction. 2,3 These injuries typically occur in younger patients as a result of flexion distraction forces on the spine and are associated with multisystem injuries. 4 We describe the presentation and management of a patient with bilateral lumbar facet dislocation with severe radiculopathy treated by using a posterior surgical decompression with short segmental reduction with instrumented fusion followed by an anterior interbody fusion through a lateral approach.…”
Section: Introductionmentioning
confidence: 99%
“…Following the anterior procedure, we felt a short segment posterior arthrodesis across L5-S1 would be adequate to stabilize the L-S dissociation and proceeded with a posterior lumbar fusion. Both procedural techniques have been extensively published in the literature, with a range and variety of implants and instruments that can be utilized [6][7][8][9]. With the posterior procedure, the ligamentous complex was disrupted and there was a large gap in the lamina of L5-S1.…”
Section: Figure 3: Intraoperative Lateral X-ray Following the Anteriomentioning
confidence: 99%
“…Aihara et al reported a 68.4% rate of neurologic deficit in 57 cases [ 1 ], while only 3 out of 11 patients (27.3%) in the series by Vialle et al demonstrated neurological injury [ 58 ]. Grivas et al reported a 58% rate of neurologic deficit for all lumbosacral fracture dislocations [ 2 ], while Arandi et al found an 89% rate of neurological injury for complete lumbosacral dislocations [ 59 ].…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Traumatic lumbosacral dislocation is a rare clinical entity, characterized by unilateral or bilateral facet dislocations causing displacement at the level of the fifth lumbar vertebra in relation to the sacrum [ 1 ]. This injury pattern is caused by high-energy mechanisms such as motor vehicle collisions, falls from height, and crush injuries and is frequently associated with severe concomitant injuries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%